A MORPHOMETRIC EVALUATION OF HUMAN KERATINIZED MUCOSA - STATISTICAL STUDY - Simona Andreea Moraru; Vanda Roxana Nimigean; Daniela Gabriela Bălan; Victor Nimigean (Amaltea Medical Publishing House, 2018)
This study presents statistically processed morphometric data on maxillary and mandibular keratinised mucosa height and some clinical considerations. Measurements were performed at incisive, premolar and molar levels, in the maxillary and the mandibular jaws, in 31 patients (21 women and 10 men). The results obtained were centralised and the mean values of the keratinised mucosa height were determined, which were graphically presented. These results were then discussed by comparing with the findings in other studies.